Lazarus of Bethany: Suspended animation or final death? Some aspects of patristic and modern exegesis - Barkhuizen, J. H. (Hervormde teologiese studies, 1995)
This paper comprises two aspects; In the first part the unique character of the miracle of the resurrection of Lazarus is outlined, especially from the perspective of patristic exegesis. In the second part patristic exegesis, together with grammatical and semantic analysis, is taken as basis of argumentation — against an example of modern exegesis — as to how modern man should define and interpret this event in the life of Jesus.